Circulating Microrna-19 as a Non-Invasive Biomarker for Detecting Lung Cancer: A Systematic Review and Meta-Analysis of Diagnostic Test Accuracy Studies - Farida Anggraini Soetedjo; Nur Khamidah; Johanes Aprilius Falerio Kristijanto; Febrisma Bangun Sanjaya (Green Publisher Indonesia, 2025)
Invasive procedures remain the gold standard for lung cancer diagnosis, while new cases in 2018 reached 30,023 patients and tend to occur at a younger age, necessitating non-invasive markers for early detection of lung cancer. Currently, numerous studies have been conducted on microRNA (miRNA) as a lung cancer biomarker, including miRNA-19; however, research findings on miRNA-19 in the diagnosis of this disease remain controversial, prompting this study to assess the ability of miRNA-19 to detect lung cancer through a meta-analysis. Literature searches were conducted in three databases (PubMed, Science Direct, and Cochrane) up to March 22, 2023, using the Patient, Intervention, Comparison, Outcome (PICO) principle, with inclusion criteria for prospective, retrospective, case-control, or cross-sectional studies providing data for analyzing the diagnostic capability of miRNA-19. The methods used adhere to the 2020 PRISMA guidelines. Analysis was performed using STATA, MetaDisc, and Review Manager software. Four articles met the inclusion criteria for this meta-analysis. The combined analysis results regarding the sensitivity of miRNA-19 in lung cancer diagnosis reached 0.81 (95% CI [confidence interval]: 0.76–0.85), specificity 0.69 (95% CI: 0.61–0.76), diagnostic odds ratio (DOR) 12.62 (95% CI: 4.73–33.65), and area under the curve (AUC) 0.85. Analysis of the positive likelihood ratio (PLR) and negative likelihood ratio (NLR) yielded results... Analysis of the positive likelihood ratio (PLR) and negative likelihood ratio (NLR) yielded results 2.51 (95% CI: 1.59–3.95) and 0.29 (95% CI: 0.18–0.48). Based on the above data, miRNA-19 has potential in the non-invasive diagnosis of lung cancer.